MULTIPLIKASI TANAMAN NILAM (Pogostemon cablin Benth) var. TAPAK TUAN SECARA IN VITRO - ASIYAH, SITI; TUMILISAR, CHRISTIANI; LESTARI, TUTI (Bioma, 2015)
ABSTRACTTissue culture is a technique widely used for propagation and improvement of crop quality. One way of plant propagation can be done with in vitro techniques. The purpose of the study was to determine the combinations and concentrations of NAA and BAP are appropriate for plant propagation patchouli. Dependent variable is the time of initiation of callus and shoots, callus texture, color callus, shoot number, and the number of roots patchouli. Independent variable is the concentration of growth regulators NAA and BAP. The method in this study is the experimental method. Data were analyzed by two-way Anova test followed by Duncan’s Multiple Range Test (DMRT). The results showed the stem explants concentrations of NAA and BAP best to induce callus is without NAA and BAP (control), 0.1 ppm NAA without BAP, NAA + BAP 0.5 ppm 0, while the leaf explants is there a 0.1 ppm NAA without BAP, NAA 0.1 ppm BAP + 0.5 ppm, 0.5 ppm BAP without NAA and NAA + BAP 0:01 ppm 1 ppm. Highest number of shoots obtained at a concentration of 0 ppm NAA concentration and NAA and 0.01 for leaf explants at a concentration of 0:01 ppm NAA + BAP 1 ppm and 0 ppm NAA + BAP 0.5 ppm for stem explants. Highest number of roots was found in 0:01 ppm for NAA concentration and leaf explants at a concentration of 0.1 ppm NAA + BAP and NAA 00:01 0 ppm ppm + 0.5 ppm BAP stem explants. Results of statistical analysis showed that there were significant differences of NAA and BAP concentrations on plant propagation patchouli (Pogostemon cablin Benth). Keywords: tissue culture, NAA, BAP, plant nilam (Pogostemon cablin Benth)